Clinical Features and Outcome of Thrombotic Microangiopathies: Comparison between Patients with and without Malignancy - Van de Louw, Andry; Cohrs, Austin; Leslie, Douglas (Thrombosis and Haemostasis, 2020)
Thrombotic microangiopathy (TMA) is an uncommon complication of cancers, related to the malignancy itself, antineoplastic drugs, or hematopoietic stem cell transplant. It was reported mostly as case series but large data are lacking. We used the large U.S. MarketScan database to compare TMA between patients with and without malignancy. Adult patients hospitalized between 2005 and 2014 with a diagnosis of TMA were included; cancer patients were defined by a diagnosis of cancer within 1 year prior to or during the admission with TMA. Associated inpatient diagnoses, procedures, hospital mortality, and long-term survival were collected. We included 3,227 patients; 617 (19.1%) had cancer (age 54 [44–60] years, 58% female), which was a new diagnosis for 23% of patients. Two-thirds of cancer patients had solid tumors (mostly pancreas, lung, breast, colorectal, and hepatobiliary, half of them metastatic) and one-third had hematological malignancies (lymphoma, acute leukemia, and multiple myeloma); TMA patients with cancer were older, more often men, had more noncancer-related comorbidities, and developed more sepsis and coagulopathy than TMA patients without cancer. Hospital mortality was significantly higher in cancer patients (16.6% vs. 6.1%, p < 0.001) and reached 30% in transplant recipients; malignancy was an independent risk factor for hospital mortality in multivariate analysis and sensitivity analyses excluding patients with metastases or patients who did not undergo plasmapheresis led to similar results. Malignancy was also associated with decreased long-term survival.
Keywords: thrombotic microangiopathy; cancer; hematological malignancy; mortality